"Stress Control" as a Large Group Psychoeducational Intervention at Step 2 of IAPT Services: Acceptability of the Approach and Moderators of Effectiveness. Issue 4 (14th September 2015) - Burns, Paul; Kellett, Stephen; Donohoe, Gill
Abstract : Background: "Stress Control" (SC) has been adopted as a core intervention in step 2 of Improving Access to Psychological Therapies (IAPT) services, but contemporary evidence of effectiveness has lagged behind service uptake.Aims: To investigate the acceptability and effectiveness of SC and to explore moderators of outcome.Method: Analysis of acceptability (via attendance rates) and effectiveness (via IAPT minimum dataset).Results: SC was well tolerated with 73.3% of all patients and 75.4% of "clinical cases" attending three or more sessions. Of the 546 "clinical cases" attending SC and not in receipt of other interventions, 37% moved to recovery. Attendance improved outcome; for those patients attending all SC sessions the recovery rate rose to 59.2%.Conclusion: SC appears a well-tolerated and effective intervention that enables large numbers to gain access to treatment in an organizationally efficient manner. Attendance is important in facilitating SC outcomes and research evaluating attendance interventions are needed.